Tijdens de bestuursoverdracht. V.l.n.r.: Ten Berge, Moens, Van Leeuwen, Muijs, Lerner, Nachbahr, Ankum en Teulings
Tijdens de bestuursoverdracht. V.l.n.r.: Ten Berge, Moens, Van Leeuwen, Muijs, Lerner, Nachbahr, Ankum en Teulings.